Hepatic Steatosis Detection by Computer Vision During Chest Low-Dose Computed Tomography in Lung Cancer Screening Program - D. К. Zakharova; N. V. Nudnov; М. R. Kodenko; R. V. Reshetnikov; А. P. Gonchar (Вестник рентгенологии и радиологии)
Background. Chest low-dose computed tomography (LDCT) is used in lung cancer screening, but the study data can also be used to assess the liver condition, including the hepatic steatosis (HS) detection. However, radiologists often do not pay attention to liver changes due to the focus on the chest. Objective: to determine the prevalence of HS during chest LDST among lung cancer screening patients using a computer vision (CV) system. Material and methods. For a retrospective study, 300 chest LDCT were taken from Moscow lung cancer screening in 2018–2020. Hepatic attenuation analysis was performed by CV, the values < 40 HU were considered as HS. The text protocols of CT scans were analysed and compared with decreased hepatic attenuation revealed by CV system. Results. 291 patients were analysed, the median age for the sample was 65 [61; 70] years. The mean hepatic attenuation was 55.6 ± 14.8 HU. Hepatic attenuation < 40 HU was found in 13% patients (23 (16.1%) males and 14 (9.5%) females), a statistically significant difference was revealed among these patients (p = 0.04). Six (4.2%) males and 4 (2.7%) females were at risk for HS (40–45 HU). The examination of text protocols showed no pathology discovered in all cases. Conclusion. The prevalence of CT signs for HS among the lung cancer screening group in Moscow was 13%. The absence of HS in text protocols highlights the importance of using CV systems in the routine practice.